KARAKTERISTIK DAN POLA SEBARAN PHYTOTELMATA SEBAGAI TEMPAT PERINDUKAN ALAMI NYAMUK DI KEBUN RAYA LIWA LAMPUNG BARAT - Sitinjak, Mentoria Alviani; Rosa, Emantis; Agustrina, Rochmah; Sutyarso (Universitas Jambi, 2020)
Liwa Botanical Garden (KRL) is an ex-situ plant conservation area which has a large collection of plants. Therefore, there will be many types of plants in KRL that have phytotelmata. Phytotelmata is a plant in which the organs can hold water and is used by various organisms including mosquitoes as natural breeding grounds. The aim of this study was to determine the phytotelmata characteristics and phytotelmata distribution patterns in the Liwa Botanical Garden, West Lampung. This research was carried out in November 2019 - January 2020 at the Liwa Botanical Garden and the University of Lampung Botanical Gardens. The study was conducted descriptively with a survey method approach. The data obtained is displayed in tables and figures. The results showed that there were 7 types of phytotelmata in the Liwa Botanical Garden namely phytothelmata in the plants of Nepenthes mirabilis, Cyathea coopei, Bambusa sp. Areca catechu, Musa sp. Colocasia gigantea, and Crynum asiaticum with 2 phytotelmata distribution patterns: in groups with IP values ranging from 0.813-1,194 and uniform distribution patterns with IP values of -2.08.Keywords: Phytotelmata, Natural Breeding Ground, Kebun Raya Liwa.